Association of Apolipoprotein A-V Gene Polymorphisms and Lipid Metabolism in Mongolian Patients with Metabolic Syndrome (Central Asian Journal of Medical Sciences, 2017)
Objectives: Our study determined the genetic effect of Apolipoprotein A-V (APOA5) gene polymorphisms on lipid parameters in patients with metabolic syndrome (MetS). Methods: 160 patients with MetS and 144 healthy individuals were selected for the case and control groups, respectively. APOA5 gene polymorphisms (-1131T>C, IVS3+476G>A, c.1177C>T, c.1259T>C) were genotyped using PCR-RFLP. Results: Serum levels of total cholesterol and triglyceride were higher in the MetS group than the control group (p=0.028, pC, IVS3+476G>A, c.1177C>T. Conclusion: Our results suggest that, among the APOA5 SNPs, the C allele of -1131T>C polymorphism is a risk factor for MetS.